PENGARUH KOMITMEN PIMPINAN DAN ETIKA KERJA TERHADAP KINERJA KARYAWAN PT. GERAHA KERINDO UTAMA JAKARTA - Dr. Ismail Razak, M.Si.; Mohamad Idham Maulani (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
The aim of this study was to analize the influence of commitment of leaders and work ethic on the employee performance of PT. Geraha Kerindo Utama, Jakarta. Secondary data was obtained from PT. Geraha Kerindo Utama, while primary data was obtained from employee of PT. Geraha Kerindo Utama through admission filling of questionnaire by using scale of Likert. In this study, simple random sampling method was used and data analysis method was simple linear regression and multiple linear regression. The results of this study indicated that commitment of leaders and work ethic positively and significant influenced the employee performance of PT. Geraha Kerindo Utama. The conclution of this study is that commitment of leaders was dominant than work ethic in influencing the employee performance of PT. Geraha Kerindo Utama.